2009
DOI: 10.1155/2009/495863
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Induced Hematologic Syndromes

Abstract: Objective. Drugs can induce almost the entire spectrum of hematologic disorders, affecting white cells, red cells, platelets, and the coagulation system. This paper aims to emphasize the broad range of drug-induced hematological syndromes and to highlight some of the newer drugs and syndromes. Methods. Medline literature on drug-induced hematologic syndromes was reviewed. Most reports and reviews focus on individual drugs or cytopenias. Results. Drug-induced syndromes include hemolytic anemias, methemoglobine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
79
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(85 citation statements)
references
References 94 publications
3
79
0
2
Order By: Relevance
“…These results also apply to hemoglobin values shown in table (5) this indicates an obvious anemia in the treated groups this supports findings of [18], where there were significant decrease in values of RBC and Hb While [7] pointed out that there are no significant differences, [2] confirmed that there were few effects of omeprazole causing anemia. In general, an increase in the duration of taking any medicine has side effects where they cause disorders in red cells, platelets, and the coagulation system [17], It is also known that the basic function of erythrocytes is to transport hemoglobin and the low concentration of hemoglobin in the blood is evidence of anemia [3] This confirms the apparent effect of Omeprazole in the current work. Table (4) also shows variation test among and within the three groups.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…These results also apply to hemoglobin values shown in table (5) this indicates an obvious anemia in the treated groups this supports findings of [18], where there were significant decrease in values of RBC and Hb While [7] pointed out that there are no significant differences, [2] confirmed that there were few effects of omeprazole causing anemia. In general, an increase in the duration of taking any medicine has side effects where they cause disorders in red cells, platelets, and the coagulation system [17], It is also known that the basic function of erythrocytes is to transport hemoglobin and the low concentration of hemoglobin in the blood is evidence of anemia [3] This confirms the apparent effect of Omeprazole in the current work. Table (4) also shows variation test among and within the three groups.…”
Section: Discussionsupporting
confidence: 79%
“…After orally administration, Omeprazole is absorbed from the small intestine and carried by the blood to the parietal cell of the stomach [22]. There are many studies on omeprazole Most of these studies relate to the histological effect on the digestive system [23]; [9] , as for studies of its effect on blood, they are very few, [15] recorded no significant effect of omeprazole on blood, [5] mentioned that 22 hematological effects: leucopenia and agranulocytosis have been reported but Most studies indicate no significant effect of Omeprazole on blood, generally Excessive use of medicines can cause hematologic effects [17] ; [14] In another study, there was a clear effect of omeprazole on blood [2]. The aim of this study is to assess the effect of long-term taking of Omeprazole drug on the blood picture by performing some hematological parameters.…”
Section: Introductionmentioning
confidence: 99%
“…It can be a result of direct damage or consumption of peripheral blood cells or decreased production of blood cells in the bone marrow, commonly referred to as bone marrow suppression or myelotoxicity (11). In vitro treatment of hPBMC with palbociclib showed no direct cytotoxicity up to 10 mmol/L supporting that the mechanism is through bone marrow suppression (Supplementary Fig.…”
Section: Mechanism Of Bone Marrow Toxicitymentioning
confidence: 91%
“…Among anticonvulsant drugs diphenyldrantoin, carbamazepine are documented to cause PRCA. Pathogenesis is thought to be by immune dysfunction with antibodies directed against erythroid precursor cells or erythropoietin, or due to T-cell mediated suppression of erythropoiesis [1]. Aplastic anemia, leukopenia and thrombocytopenia are some of the serious hematological adverse effects of valproic acid therapy cited in the literature [2,3].…”
Section: Discussionmentioning
confidence: 99%
“…Neutropenia, thrombocytopenia, aplastic anemia are known haematological manifestations [1]. We present a case of severe symptomatic Pure Red Cell Aplasia (PRCA) secondary to sodium valproate monotherapy prescribed for absence seizure.…”
Section: Introductionmentioning
confidence: 99%